Finite elements analysis suggests a defensive role for osteoderms in titanosaur dinosaurs (Sauropoda) - Silva Junior, Julian C.G.; Montefeltro, Felipe C. [UNESP]; Marinho, Thiago S.; Martinelli, Agustín G.; Langer, Max C. (Elsevier, 2022)
Here we present, for the first time, the use of finite element analysis to evaluate bites of two possible predators, a baurusuchid crocodyliform and an abelisaurid theropod into titanosaur osteoderms, in order to test if these structures could act as defensive tools. Our results showed that bites caused much less stress on osteoderms that did not went through internal resorption and were composed mainly by solid bone. Our data strengths the hypothesis that titanosaur osteoderms could have provided more functions than just mineral storage.
Keywords: Finite elements analysis; Osteoderms; Sauropoda; Titanosauria